Perceptions of Good Jobs : Analytical Report--Risaralda, Colombia - Bjørkhaug, Ingunn (World Bank, Washington, DC, 2013)
This study shows how jobs are perceived in Risaralda, Colombia, by exploring beyond the earnings, health benefits, and pension plans that characterize a “good job” to focus on the features that increase living standards, productivity growth, and social cohesion. Colombia has experienced conflict for over 60 years, and for both communities and individuals, stable income, jobs, and social security can provide the means for survival and recovery. Men are more likely to work than women, with middle-aged people working more frequently, while prolonged health problems hinder employment. Urban households with a higher number of working adults are better off—though this relationship between wealth and employment is not clear in rural areas—and strong linkages exist between job stability and benefits. Assessments of job satisfaction show job meaningfulness determines the level of satisfaction. Middle-aged people are more satisfied than both younger and older people, and wealthier workers are more satisfied than the less wealthy. Jobs consist mainly of manual labor—dominated by routine work with a relatively high level of autonomy—and a “good,” more meaningful jobrequires a shift from manual toward more cognitive work, from routine toward more creative tasks. Having a wage job increases the level of social trust, contributing to social cohesion, though the unemployed have higher confidence in institutions.